PEMANFAATAN TERAPI SHIATSU SEBAGAI TINDAKAN PREVENTIF CEDERA OTOT - Nasywa Yudeldi; Ade Teti Vani; Dessy Abdullah; Rosmaini, Rosmaini; Nadia Purnama Dewi; Yuliza Birman; Melya Susanti; Rinita Amelia (Nusantara Hasana Journal, 2025)
Shiatsu therapy is a complementary treatment approach rooted in Japanese tradition, based on the principle of applying pressure to specific points on the body to stimulate energy flow, improve health, and support well-being. This study aims to explore the effect of shiatsu therapy on reducing the risk of injury. This study utilized a qualitative methodology, conducting a literature review of journals published between 2015 and 2025 related to shiatsu therapy. The search employed the keywords "shiatsu massage," "shiatsu for muscle injury," and "effect of shiatsu." Findings from the literature were synthesized and presented in narrative form The findings indicate that shiatsu therapy may reduce the risk of injury by decreasing muscle tension, enhancing flexibility, and increasing range of motion. Furthermore, shiatsu therapy is associated with psychological benefits, including reduced stress and improved sleep quality, both of which are crucial for recovery. Therefore, shiatsu therapy represents a potential strategy for injury prevention and comprehensive health maintenance.